Pathophysiology of Pain Pathogenesis, Mechanism, Pathology Prognosis - Khidirovna, Lapasova Zebo (American Journal of Bioscience and Clinical Integrity, 2025)
Pain is the most common symptom that causes suffering to millions of people worldwide. The treatment and elimination of pain is one of the most important tasks, comparable in importance to life-saving measures. What is pain? The International Association for the Study of Pain defines pain as: “Pain is an unpleasant sensory and emotional experience associated with actual or potential tissue damage, or described in terms of such damage.” Pain is a specific psychophysiological state of a person, which occurs as a result of the action of extremely strong or destructive stimuli and causes functional or organic disorders in the body. The word "disease" itself is directly related to the concept of "pain". Pain should be considered as a stress factor, which activates functional and metabolic systems with the participation of the sympathetic nervous system and the hypothalamic-pituitary-adrenal cortex system. These systems provide protection of the body from the effects of pathogenic factors. Pain includes such components as consciousness, emotion, motivation, feelings, as well as vegetative, somatic and behavioral reactions. The perception and perception of pain is based on nociceptive and antinociceptive mechanisms.